Study Of Prevalence of Diarrheal Diseases Amongst Under Five Population - Sutariya, Shailesh; Talsania, Nitiben; Shah, Chintul (National Journal of Community Medicine, 2011)
Acute diarrheal disease with its accompanying dehydration has remained a challenging problem to the medical profession and the community in the third world countries especially in the age below five years. The current study was conducted to study the prevalence of diarrheal diseases amongst under five population and the seasonal distribution of diarrheal diseases amongst under five population. It was a longitudinal study conducted among 2408 children under 5 yrs age group including 541 infants. Maximum cases of diarrhea (81.89%) were in infants. 90.60% episodes of diarrhea were treated at home with ORS and/or home available fluids. About half of the diarrheal episodes 2798 (46.39%) were occurred in monsoon season.